Efectos de sustratos y abonos foliares en el crecimiento inicial de samanea saman (jacq.) merr. (Samán) - Zambrano Caicedo, Michelle Jamilet (2024)
The production of quality seedlings in nurseries has become indispensable to guarantee uniform and well-developed plants, ensuring the success of future planting. To obtain quality seedlings in nurseries, it is necessary to use a good substrate and the application of fertilizers, among which are foliar fertilizers. Therefore, the objective of this research was to evaluate the effects of substrates and fertilizers on the initial growth of S. saman seedlings. A factorial experiment (2 fertilizers x 3 substrates) with three replications, established on a Completely Randomized Design (CRD), was used. The combinations evaluated were the following: T1= Nitrofoska + (Black soil + River sand); T2 = Nitrofoska + (Black soil + Peanut husk + River sand); T3 = Nitrofoska + (Black soil + Rice husk + River sand); T4 = Yaramila Complex + (Black soil + River sand); T5 = Yaramila Complex + (Black soil + Peanut husk + River sand); T6 = Yaramila Complex + (Black soil + Rice husk + River sand). The results of germination and survival indicated that the proposed pre-germinative treatment (which treatment, indicate), became evident 5 days after establishment in the planting bed. The averages obtained after 10 days indicated that the substrate influenced seedling height and number of leaves; the best averages for height and number of leaves were for the first 10 days of establishment.